First record of the genus Dermatobranchus van Hasselt, 1824, in the Mediterranean Sea (Nudibranchia: Arminidae) - COLUCCI, G.; STRAFELLA, R.; TRAINITO, E.; DONEDDU, M. (Mediterranean Marine Science, 2015)
Three individuals of a nudibranch belonging to the genus Dermatobranchus (Arminidae) were found at a depth of 3 meters, in a bottom with sand and gravel, during night SCUBA diving activity in Porto Pirrone, Leporano (Taranto, Apulia, Italy). The external morphology and coloration of these Mediterranean individuals clearly resemble those of D. rubidus (Gould, 1852), a species known only from the central and western Pacific Ocean. This is the first record of the genus Dermatobranchus van Hasselt, 1824 for the Mediterranean Sea.